Blood Oxygen Saturation After Ischemia is Altered With Abnormal Microvascular Reperfusion. (May 2015) - Adingupu, Damilola D.; Thorn, Clare E.; Casanova, Francesco; Elyas, Salim; Gooding, Kim; Gilchrist, Mark; Aizawa, Kunihiko; Gates, Phillip E.; Shore, Angela C.; Strain, David W.
Abstract: Objective: We have previously described a distinct abnormality in the cutaneous microcirculation that is characterized by an abnormal reperfusion response following an ischemic stimulus. We investigated the physiological significance of this abnormality; by measuring microvascular perfusion and blood oxygen saturation in groups stratified by three distinct reperfusion responses. Methods: Cutaneous microvascular reperfusion after four minutes of arterial occlusion above the ankle was measured on the foot using laser Doppler fluximetry and optical reflectance spectroscopy in almost 400 adults. Individuals were stratified into three groups according to the microvascular reperfusion response: normal and two abnormal patterns (DEP and NDEP). Results: Our main findings were that abnormal microvascular reperfusion responses (DEP and NDEP) had a higher baseline oxygen saturation ( p = 0.005), a lower plateau in oxygen saturation ( p < 0.0001 and <0.0001, respectively), lower oxygen saturation area under the curve ( p < 0.0001 and <0.0001), a longer time to reach oxygen saturation plateau ( p = 0.002 and 0.001), and a longer time to initiate an increase in oxygen saturation ( p = 0.007 and 0.001) compared to normal. Differences remained after adjustment for confounding variables. Conclusions: Individuals with abnormal microvascular reperfusion had a markedly altered pattern of oxygen increase during reperfusion. We propose that this may represent dysfunctional microvascular autoregulation that is clinically important in the etiopathology of target organ damage.